PENGELOLAAN SEKOLAH BERBASIS ISO 9001:2000 DI SMKN 1 SURAKARTA - PANCANINGRUM , NOVITA (2011)
The purposes of recent research are: (1) To recite the administration service characteristic for pupil by school based ISO 9001:2000 at SMKN 1 Surakarta, (2) To recite the service characteristic of tool and infrastructure use for pupil by school based ISO 9001:2000 at SMKN 1 Surakarta, and (3) To recite the service characteristic of tool and infrastructure maintenance for pupil by school based ISO 9001:2000 at SMKN 1 Surakarta. This recent research is designed and analyzed in qualitative approach to recite the school management based ISO 9001:2000 at SMKN 1 Surakarta. The data collection techniques of recent research are conducted by observation, documentation, and depth interview with a number of informants. The technique used in data analysis is arranged data in a site, Miles and Huberman's theory. Existing data are grouped, selected, and then analyzed in the form of picture. This is used to solve fundamental questions, and then elaborated in the form of descriptive language. Result: (1) Administrative services to participant educated by SMKN 1 Surakarta are executed by preparing human resource to fulfill the needs that support study process. The needs are used up goods, class inventory, key loaning, and correspondence. (2) Service of study facilities and basic facilities usage is executed by duty division and clear responsibility. The lab. manager arranges the schedule and make usage of regulation lab. The teachers help learning process in lab. (3) Service of study facilities and basic facilities treatment is executed with involvement of all stakeholders. Treatment is conducted to software and computer hardware.